PERANCANGAN HOTEL LIMA BELAS LANTAI DI BANJARMASIN - Bengawan L. Kosasih (Universitas Lambung Mangkurat, 2014)
Multy story building is a building that has more than one floor. The higher the more complicated calculation of construction. In this final project, entitled